A Method for Measuring the Optical Parameters of Deep-Sea Water - Balasi, Konstantia G.; Lenis, Dimitrios; Maniatis, Manolis; Maragos, Nikolaos; Stavropoulos, Georgios (Frontiers in Physics, 2018)
The accurate knowledge of the optical properties of deep-sea water is of great importance for the neutrino event reconstruction process in underwater cosmic neutrino telescopes. In this study we present a method to measure the parameters describing the absorption and scattering characteristics of deep-sea water. The device, specifically developed and deployed for measuring the aforementioned parameters, is described. The experimental measurements are presented and the obtained results are discussed.